2009
DOI: 10.1103/physrevb.80.174406
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of electrically induced magnetic reconstruction at the manganite/ferroelectric interface

Abstract: The control of magnetization via the application of an electric field, known as magnetoelectric coupling, is among the most fascinating and active research areas today. In addition to fundamental scientific interest, magnetoelectric effects may lead to new device concepts for data storage and processing. There are several known mechanisms for magnetoelectric coupling that include intrinsic effects in single-phase materials, straininduced coupling in two-phase composites, and electronically driven effects at in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
221
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 57 publications
25
221
2
Order By: Relevance
“…As a result, a modulation of the LSMO Curie temperature T C , from 248 to 263 K, as well as of the magnetization M upon the ferroelectric switching, is clearly observed. Theoretical studies, undertaken on similar complex oxide heterostructures, confirmed that P switching, inducing an electrostatic depletion or accumulation of carriers at the interface between the two oxides, produces an alteration of the interfacial spin [16] and/or orbital [17,18] configurations inherent to the interfacial Mn ions, which in turn is capable to modulate the magnetic properties of the system. Moreover, a similar T C modulation by switching the LSMO layer from the depletion to the accumulation state was previously reported [8,19], but here it occurs at a much higher temperature.…”
Section: Resultsmentioning
confidence: 97%
“…As a result, a modulation of the LSMO Curie temperature T C , from 248 to 263 K, as well as of the magnetization M upon the ferroelectric switching, is clearly observed. Theoretical studies, undertaken on similar complex oxide heterostructures, confirmed that P switching, inducing an electrostatic depletion or accumulation of carriers at the interface between the two oxides, produces an alteration of the interfacial spin [16] and/or orbital [17,18] configurations inherent to the interfacial Mn ions, which in turn is capable to modulate the magnetic properties of the system. Moreover, a similar T C modulation by switching the LSMO layer from the depletion to the accumulation state was previously reported [8,19], but here it occurs at a much higher temperature.…”
Section: Resultsmentioning
confidence: 97%
“…An interesting prediction was made recently for the La 1−x A x MnO 3 /BaTiO 3 (001) interface, where A is a divalent cation [121]. First-principles calculations showed a possibility to switch a magnetic order at the interface from FM to AFM by reversing the polarization of BaTiO 3 .…”
Section: (A) Interface Magnetizationmentioning
confidence: 92%
“…Such complex interplay between the spin (magnetism), lattice (strain), charge (electrostatic) and orbit (e.g. charge-driven interfacial orbital hybridization [45][46][47][48][49][50] or reconstruction [51][52][53][54][55]) across the interface of the multiferroic heterostructure would be a very interesting but tough issue. -The mesoscale mechanism of such voltage-controlled magnetism in multiferroic heterostructures is also important.…”
Section: Discussionmentioning
confidence: 99%
“…the converse magnetoelectric (ME) effect, has become a central issue in the fields of spintronics and multiferroics [1][2][3][4][5][6][7][8][9][10]. It can provide a fast and extremely energy-efficient way for modulating magnetism compared with the traditional way of using external magnetic fields or spin currents [11], and has thus tremendous potential in future low-power and [ [51][52][53][54][55] (for details, see comprehensive review [10]). Compared with the strains which can normally be sustained throughout the heterostructure [5][6][7][8], such charge-driven ME effects can only occur at the heterointerface ranging from the first few atomic layers to several nanometres (normally less than 10 nm) depending on the charge screening length of a specific magnetic film [9,10].…”
Section: Introductionmentioning
confidence: 99%